Antaseden Minat Penggunaan Bank Aladin Syariah : Pendekatan Teori TAM 3 - Setyaningrum Adji, Bryllian Octaviani; Widyaningrih, Meilana (Masoem University, 2025)
This research was investigated to determine the influence of digital literacy, perceived usefulness, and perceived convenience on interest in using Aladin sharia banking services in Surakarta using TAM 3 theory. The research method used is quantitative method. Then for sampling using non probability techniques with purposive sampling techniques. In this study the population size is unknown so it uses the lemeshow formula. This study shows that partially, digital literacy, perception of usefulness and perception of ease of use have a positive and significant influence on interest in using Bank Aladin Syariah services. Simultaneously, the attachment between digital literacy, perception of usefulness, and perception of convenience can be seen from the R value and the Adjusted R Square value which shows that all X variables are able to contribute 79.3% to the Y variable, and the remaining 20.7% comes from the variables that were not studied.